Implementasi Terapi Muhasabah untuk Mengurangi Perilaku Bullying pada Remaja di Desa Klakahrejo, Surabaya - Faiza, Lailatul; Albaar, Ragwan (YASIN, 2025)
The phenomenon of bullying among adolescents is a social issue with serious implications for psychological, social, and emotional development, thus requiring appropriate and contextually relevant interventions. This study aims to examine the effectiveness of muhasabah therapy as a counseling approach to reduce bullying behavior among adolescents in Klakahrejo Village, Surabaya. A qualitative approach with a case study design was employed, involving observation and in-depth interviews with individuals identified as perpetrators of bullying. Muhasabah therapy was implemented through a systematic process comprising problem identification, diagnosis, prognosis, treatment, and evaluation. The therapeutic process focused on six main steps: goal setting (musyarathah), self-control (muraqabah), self-reflection (muhasabah), self-sanctioning (mu’aqobah), commitment to change (mujahadah), and desire management (mu’atabah). The findings indicate positive changes, including a decrease in verbal bullying behavior, enhanced self-reflection abilities, and improved peer relationships. These results suggest that muhasabah therapy is effective in helping adolescents manage negative behaviors, enhance spiritual awareness, and strengthen social responsibility. In conclusion, muhasabah therapy holds potential as a practical alternative strategy in Islamic counseling for addressing bullying behavior among adolescents.